Bibliodrama: Um acesso à Bíblia no contexto pedagógico - Daunis, Roberto (2013)
The use of Bibliodramas in Christian groups serves to help relate the Bible texts with the real daily lives of people and to bring these texts closer to their lives. This approach presupposes an adequate pedagogical practice that considers the biblical text and the individual and group life experience of the people that are dealing with the texts, integrating the various dimensions of knowledge. The study points out details to be observed in relation to the participants and in relation to the role of the leadership in Bibliodrama groups.